A place of psikhofiziologichnoy examination is with the use of poligrafa in the criminal legal proceeding of Ukraine - Мотлях, Олександр Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article a question is examined in relation to the place of judicial psikhofiziologichnoy examination with the use of poligrafa in the criminal legal proceeding and correlation of this sort of examinations with the traditionally acknowledged judicial examinations.